Race and payor type for child visits with public health dental hygienist practitioners. (10th August 2021) - Burgette, Jacqueline M.; Ok, Sally H.; Ray, Kristin N.; Faulds, Samantha; Stiles, Amy; Hoberman, Alejandro; Martin, Brian
Abstract: Purpose: To examine whether growth in visits to public health dental hygiene practitioners (PHDHPs) providing preventative dental services at a pediatric hospital clinic was predominantly among children receiving public insurance and children of minority background from 2013 to 2017. Methods: Longitudinal descriptive data analysis from electronic health records for 6856 children under age 18 years who visited PHDHPs co‐located at a hospital clinic in Pittsburgh, PA, from 2013 to 2017. We compared visits between white versus non‐white children and between children with public, private, and no or missing insurance by year. Results: Visit volume doubled from 2013 ( n = 811) to 2017 ( n = 1868). The proportion of PHDHP visits with non‐white children increased from 77% ( n = 625) in 2013 to 87% ( n = 1472) in 2017 ( p < 0.001). The proportion of PHDHP visits with children with public insurance increased from 72% ( n = 585) in 2013 to 82% ( n = 1377) in 2017 ( p < 0.001). Conclusions: PHDHPs co‐located at a pediatric hospital clinic saw a high proportion of visits from children of non‐white race and with public insurance. Visits from children of minority race and with public insurance increased disproportionately as visit volume grew from 2013 to 2017, depicting a vehicle through which historically underserved children increasingly accessed preventive dental services.